Sustainability and research in the Colombian-Ecuadorian public higher education system - Marco, Burbano-Pulles; Orlando, Meneses-Quelal (Frontiers in Education, 2026)
The main objective of this study was to analyze the sustainability orientation of research models in four public higher education institutions (HEIs) located in the border area between Ecuador and Colombia. Using a previously validated instrument based on the Delphi methodology, data were collected from the heads of the research units of these HEIs. Statistical analysis revealed no significant differences between the research models of the four institutions and the principles of sustainability in general. However, one institution showed significantly superior performance in the environmental and economic dimensions, suggesting a better integration of sustainability criteria into its research model. The main methodological contribution of this study lies in the comprehensive characterization of HEI research models by assessing multiple indicators in four key dimensions: environmental, social, economic and institutional. This pioneering analysis contributes to the understanding of the integration of sustainability in public HEI research models in a frontier context, a topic scarcely addressed in the specialized literature. The findings have practical implications, providing HEIs with empirical evidence to critically evaluate and improve their research models, aligning their priorities with the Sustainable Development Goals (SDGs).